Implementasi Manajemen Bisnis Dalam Novel Lupus: Lupus n’Work Karya Hilman - Anantaprima, Fachrezi; Baehaki, Fikri Imam; Kurniawan, Eva Dwi (FEB Universitas Maritim Semarang, 2024)
Business management is the science and practice that encompasses planning, organizing, directing, and controlling organizational resources to achieve established goals. It involves coordinating various aspects of business activities to ensure the sustainability, growth, and success of the organization. In the novel titled